2007
DOI: 10.1537/ase.060206
|View full text |Cite
|
Sign up to set email alerts
|

Non-metric dental variation of Sakishima Islanders, Okinawa, Japan: a comparative study among Sakishima and neighboring populations

Abstract: Twenty-four non-metric tooth crown traits of Miyako and Ishigaki Islanders, from the southernmost Ryukyu Islands, were investigated and compared with those of neighboring populations. The frequency of double-shoveling in Sakishima samples, and especially, Ishigaki Island, is lower than that found among Atayal people (Taiwan) and main-island Japanese. The frequencies of protostylid and cusp 6 in Miyako and Ishigaki Islanders are comparable to those in Hokkaido Ainu and lower than in main-island Japanese and Ata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Indeed, relatively few studies have examined the population structure of the inhabitants of the Ryukyu Islands to date. However, of the studies that have been undertaken, some have reported the existence of local variations in morphological and genetic characteristics (Naito 1976;Omoto et al 1976;Haneji et al 2007;Toma et al 2007;Matsukusa et al 2010). However, the population structure within the Ryukyu Islands remains unclear due to a lack of comprehensive data and due to incompatibilities between the findings of previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, relatively few studies have examined the population structure of the inhabitants of the Ryukyu Islands to date. However, of the studies that have been undertaken, some have reported the existence of local variations in morphological and genetic characteristics (Naito 1976;Omoto et al 1976;Haneji et al 2007;Toma et al 2007;Matsukusa et al 2010). However, the population structure within the Ryukyu Islands remains unclear due to a lack of comprehensive data and due to incompatibilities between the findings of previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all studies have supported the Ainu‐Ryukyu common origin theory. Many studies do not support the theory from the viewpoint of somatology (Suda, 1950; Terakado, 1976; Ikeda & Tagaya, 1980), craniometry (Hsü, 1948; Ikeda, 1974; Tagaya and Ikeda, 1976; Pietrusewsky, 1994, 1999, 2004; Doi et al , 1997; Doi, 1998, 2003, 2004; Asato & Doi, 1999), cranial nonmetric traits (Mouri, 1986; Dodo, 1992; Dodo et al , 1998, 2000), dental morphology (Manabe et al , 1999a, 1999b, 2001, 2003a, 2008; Higa et al , 2003; Haneji et al , 2007), mitochondrial DNA (Horai et al , 1996), and the human leukocyte antigen (HLA) gene (Hatta et al , 1999; Tokunaga, 2003). Thus, even among studies involving similar methods, no consensus has been reached with regard to the genealogical position of the Nansei islanders in the Japanese archipelago and East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, plaster casts of permanent dentition ( Figure 1A) were obtained from 102 individuals at Showa University Dental Hospital, Tokyo, and from 100 individuals in Sakishima Islands (Miyako and Ishigaki), the southernmost Ryukyu Islands (Figure 2). 27,28 The Sakishima subjects were selected as individuals who had no ancestor derived from other regions for at least three generations. We also collected a blood, buccal mucosa, or saliva specimen from each individual to prepare a DNA sample.…”
mentioning
confidence: 99%
“…To reduce the metric data to a small number of dimensions, we applied a principal-component analysis (PCA) with the data for 751 Japanese individuals (375 males and 376 females) from Honshu, Okinawa, and the Sakihima Islands. 27,28,30 The procedure is as follows: the metric dental data, from which missing values were removed, were standardized for each sex. Then, merging the standardized data of both sexes, we created a correlation-coefficient matrix.…”
mentioning
confidence: 99%